Performance of Edible Mushroom Varieties Under Different Agricultural Substrates - Dollison, Mohammad D. (Future Science / FSH-PH Publications, 2023)
The study was conducted at Dr. Emilio B. Espinosa, Sr. Memorial State College of Agriculture and Technology (DEBESMSCAT) Cabitan, Mandaon, Masbate. The experimental design used was 3 x 7 CRD factorial with three varieties of mushrooms (Pink Oyster, White Abalone, and Milky Mushroom), seven agricultural substrates as treatments, Treatment A (70% rice straw and 30% sawdust), Treatment B (70% rice straw and 30% corn cob), Treatment C (70% rice straw and 30% Carbonized Rice Hull), Treatment D (100% rice straw), Treatment E (100% sawdust), Treatment F (100% corn cob) and Treatment G (100% Carbonized Rice Hull). The experiment was replicated three times with a total of 945 fruiting bags. Height, fresh weight, and the number of fruiting bodies are the data that was observed in the study. The result showed that in terms of growth performance, a nonsignificant result was observed in the height performance of the mushroom varieties inoculated in substrates with 70% rice straw, 30% corn cob, and 100% carbonized rice hull. Similarly, the number of mushroom fruiting bodies produced differed among mushroom varieties inoculated. Mushrooms inoculated in 100% carbonized rice hull attained more fruiting bodies than other tested varieties. Mushrooms inoculated in 100% corn cob produced a significantly higher number of mushroom fruiting bodies than other treatments. Finally, the weight of mushroom fruiting bodies produced in 70% rice straw and 30% carbonized rice hull applications was statistically significant for all agricultural substrates inoculated. The researcher concluded that using agricultural substrates other than carbonized rice is effective in mushroom production.